ショウワ キチ - アイスランド チジキ キョウヤクテン デ カンソク サレタ Pc3-5ガタ ミャクドウ ノ スペクトル オヨビ ヘンパ トクセイ d. ジキケンナイ ノ ULF ハドウ ダイ2カイ キョクイキ ニオケル デンリケン ジキケン ソウゴウ カンソク シンポジウム PART 1 - 岩渕, 美代子; イワブチ, ミヨコ; 福西, 浩; フクニシ, ヒロシ; 佐藤, 夏雄; サトウ, ナツオ; IWABUCHI, Miyoko; FUKUNISHI, Hiroshi; SATO, Natsuo (1980)
P(論文) 1977年7月29日-9月18日まで52日間にわたってアイスラントフサヘルおよび南極昭和,みずほ基地で観測された地磁気脈動データの解析から以下のことが明らかになった.(1)中心周波数が,20-40mHzおよび4-8mHzの2つのバントが,昼間観測される(2)f-tスペクトルの構造は,共役点で非常に類似している.(3)これら脈動の位相は,共役点でH成分がin-phase,D成分がout-of-phaseの関係を示す(4)H-D平面における楕円偏波の主軸の向きは,12MLTを境に反転するこれらの結果から昼間のPc3-5脈動は,磁気圏,境界面またはその外側でつくり出されたMHD波動が,磁気圏内に伝わり磁力線のodd-mode standing oscillationを励起させたものと考えられる. From the magnetic pulsation data recorded at the Syowa Station-Iceland conjugate pair, it is found that there are at least two pulsation bands in the Pc 3-5 frequency range in the daytime. 0ne pulsation band occurs in the 20-40 mHz range, while the other band occurs in the 4-8 mHz range, often independently of the 20-40 mHz band. The f-t spectral patterns of these pulsations are quite similar at the coniugate points, with the wave phase characteristics of odd-mode standing oscillations of local magnetic field lines. It is also found that the orientation angles of the polarization ellipses in the H-D plane switch across the magnetic local noon. These results suggest that the 20-40 mHz band and the 4-8 mHz band are standing oscillations of resonant field lines excited by external driving forces such as the Kelvin-Helmholtz instability on the magnetopause and/or the MHD waves generated near the bow shock departmental bulletin paper